VDC_100102371237.0X000001. Issue 10 (October 2018) - Seo, Young-Ji; Bailey, Katherine; Aguayo, Esteban; Juo, Yen-Yi; Sanaiha, Yas; Dobaria, Vishal; Benharash, Peyman; Lin, Anne
Readmissions occur frequently in patients undergoing ostomy creation, ranging from 12 per cent to more than 30 per cent. The objective of this study was to compare the reasons for early versus intermediate readmissions after surgical procedures involving formation of ileostomies at a national level. Patients receiving a new ileostomy were identified in the 2010 to 2014 Nationwide Readmission Database. Patients were categorized into Early, Intermediate, and Late cohorts (0–7, 8–30, 31–90 days, respectively), based on discharge-to-readmission interval. Of the 76, 590 patients undergoing ileostomy creation, 28 per cent were nonelectively rehospitalized within 90 days after discharge: 10 per cent Early, 12 per cent Intermediate, and 7 per cent Late. Compared with the Intermediate cohort, the Early readmissions were more frequently because of anastomotic complications (20% vs 12%, P < 0.001) and gastrointestinal obstruction (10% vs 5%, P < 0.001), whereas Intermediate readmissions were because of renal failure (17% vs 9%, P < 0.001). In the Late group, the most common reason for readmission was renal failure (14%), followed by anastomotic complications (11%), and stoma reversal (8%). In this nationwide study, all-cause 90-day non-elective readmissions after ileostomy procedures occurred in nearly 30 per cent of patients. Although early rehospitalizations were mainly because of surgical complications and gastrointestinal complications, late readmissions were because of ileostomy reversal.